2010
DOI: 10.1016/j.jconrel.2010.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial delivery of antioxidant enzymes loaded into non-polymeric magnetic nanoparticles

Abstract: Antioxidant enzymes have shown promise as a therapy for pathological conditions involving increased production of reactive oxygen species (ROS). However the efficiency of their use for combating oxidative stress is dependent on the ability to achieve therapeutically adequate levels of active enzymes at the site of ROS-mediated injury. Thus, the implementation of antioxidant enzyme therapy requires a strategy enabling both guided delivery to the target site and effective protection of the protein in its active … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
77
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(79 citation statements)
references
References 36 publications
1
77
0
1
Order By: Relevance
“…This same approach was used to magnetically target antioxidant enzymes to endothelial cells to protect them from oxidative stress-mediated damage [104]. These results indicate that magnetic nanoparticles with magnetic guidance may be interesting candidates for stent-targeted anti-restenotic therapies.…”
Section: Other Approaches Include the Modification Of Liposomes With mentioning
confidence: 84%
See 1 more Smart Citation
“…This same approach was used to magnetically target antioxidant enzymes to endothelial cells to protect them from oxidative stress-mediated damage [104]. These results indicate that magnetic nanoparticles with magnetic guidance may be interesting candidates for stent-targeted anti-restenotic therapies.…”
Section: Other Approaches Include the Modification Of Liposomes With mentioning
confidence: 84%
“…Chorny and co-workers [102][103][104] demonstrated that magnetic field controlled targeting of paclitaxel-loaded magnetic nanoparticles (~250 nm in diameter)…”
Section: Other Approaches Include the Modification Of Liposomes With mentioning
confidence: 99%
“…[638] Moreover, MNPs have been employed for delivering antioxidant enzymes to increase resistance to oxidative stress. [639] In contrast to permanent magnets which take advantage of the guidance response taken by MNPs, an oscillating or alternating magnetic field provides a novel on-off fashion for triggering drug release. In fact, by employing thermo-responsive polymers [640] and lipids [641] onto the surface of MNPs and exploiting the hyperthermia effect the energy transformed into heat through Brownian fluctuations and Neel fluctuations can lead to promising magnetic responsive drug delivery systems.…”
Section: Magnetic Drug Targetingmentioning
confidence: 99%
“…Cellular uptake of MNP-Ad affinity complexes by cultured vascular cells and the resultant transduction efficiency was determined after cell treatment with or without a high-gradient The feasibility of a different formulation strategy developed for encapsulation of biotherapeutics in MNP under mild conditions without the use of organic solvents was recently demonstrated with the antioxidant enzymes, catalase and superoxide dismutase, and the protective efficiency of MNP-encapsulated catalase was shown in cultured endothelial cells challenged with hydrogen peroxide (56). This formulation method, termed controlled aggregation/precipitation, is potentially applicable to both proteins and gene vectors and is based on the coentrapment of a macromolecule and nanocrystalline magnetite in the matrix of MNP formed by precipitation of calcium or zinc salts of oleic acid in the presence of a surface stabilizer, such as Poloxamer 407.…”
Section: Magnetically Targeted Delivery Of Biotherapeutics: the Desigmentioning
confidence: 99%